Ювілеї - (:unkn) unknown (Київський національний університет імені Тараса Шевченка, 2014)
Сергію Павловичу Романчуку – 70! Ростиславу Васильовичу Олійнику – 60! Ірині Михайлівні Щербань – 60! Олені Петрівні Гавриленко – 50! Марії Григорівні Онищенко – 50! Василю Васильовичу Гребіню – 50!
Keywords: Гавриленко Олена Петрівна; Гребінь Василь Васильович; Олійник Ростислав Васильович; Онищенко Марія Григорівна; Романчук Сергій Павлович; Щербань Ірина Михайлівна